2010
DOI: 10.1364/ol.35.000877
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond second-harmonic generation in periodically poled lithium niobate waveguides written by femtosecond laser pulses

Abstract: We present in this Letter the second-harmonic generation of femtosecond pulses in double-line-written waveguides fabricated in periodically poled lithium niobate (PPLN) with femtosecond laser pulses. In a 10-mm-long sample, a normalized conversion efficiency of 12.6% W(-1) cm(-2) has been achieved for 40 fs pump pulses with the wavelengths centered at 1550 nm. Simulation results show that in PPLN waveguides the FWHM of wavelength tuning curve for 40 fs pump pulses is 42 nm, which is 15 times of that for 40 ps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 10 publications
1
11
0
1
Order By: Relevance
“…In most of these applications, integrated structures like waveguides are helpful or even necessary to improve the bulk quality features. On the other hand, many techniques are applicable for waveguide fabrication in LiNbO 3 , such as Ti‐ion indiffusion , proton exchange , ion irradiation and fs‐laser inscription .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of these applications, integrated structures like waveguides are helpful or even necessary to improve the bulk quality features. On the other hand, many techniques are applicable for waveguide fabrication in LiNbO 3 , such as Ti‐ion indiffusion , proton exchange , ion irradiation and fs‐laser inscription .…”
Section: Methodsmentioning
confidence: 99%
“…The propagation losses of stress‐induced waveguides in LiNbO 3 is typically 1–3 dB/cm, which is comparable with that of the Type I waveguides. Type II structures have been fabricated in pure and doped LiNbO 3 crystals and PPLN . Also, waveguide arrays have been fabricated by a number of Type II structures, which was used for the investigation of discrete optics .…”
Section: Methodsmentioning
confidence: 99%
“…The variation of SHG CE with the central wavelength of fundamental pulse. pulses [13]. If looking into the origin of the results in Fig.…”
Section: Numerical Simulation and Discussion For Shg Of Fs Pulsesmentioning
confidence: 96%
“…Based on the plane wave and slowly varying envelope approximations, the following coupled partial differential equations can be used to describe the evolution of the fundamental and the second harmonic pulses in PPKTP waveguide [13][14][15]:…”
Section: Numerical Simulation and Discussion For Shg Of Fs Pulsesmentioning
confidence: 99%
“…% MgO-doped congruent LiNbO 3 [9], it is found that optimal grating period of 20.37 μm can be used to achieve an efficient cascaded THG under 35℃, provided that the polarization of the fundamental wave is chosen to be ordinary, and the polarizations of the SH and TH waves are chosen to be extraordinary. For the femtosecond pulses with a large spectral width, it has a large phase-matching bandwidth in the frequency conversion [10]. Therefore, the efficient SFG can still be achieved with the existence of a small wave-vector mismatch.…”
Section: Experimental Configurationmentioning
confidence: 99%